The End of the 1914–1918 War in Africa - Anne Samson (Anglica. An International Journal of English Studies)
The end of the First World War in Africa occurred at different times across the continent as the German colonies capitulated and surrendered to the allied forces between 26 August 1914 and 25 November 1918. The experience of each territory was indicative of its colonial development and local conditions. As the war inched across the landscape so people moved between states of peace and conflict, all caught up in some aspect either directly or through the provision of food and other materials. This chapter explores different experiences across the continent and the legacy of the discussions at Versailles.